Cardiovascular risk and pharmacotherapy in pediatric patients with attentiondeficit hyperactivity disorder - Ortega Delgado, Daniel Aicardo (2024)
Mental health is one of the current pillars of global health; therefore, it is considered an essential factor in the wellbeing and quality of human life. The dramatic growth in the incidence and prevalence of mental disorders has brought about a burden of silent and unsustainable disease for healthcare systems, especially in younger age groups such as children and adolescents. Although major depressive disorder, anxious syndrome, and conduct and eating disorders are some of the most frequent in this age group, attention-deficit hyperactivity disorder (ADHD) is also an entity of interest affecting between 5% and 10% of children. There exists a pharmacological treatment for this condition, and it is based on stimulant and nonstimulant medications. Evidence of the highest quality has recently demonstrated that children and adolescents who were administered ADHD medications had a higher risk of some cardiovascular event compared to those who were not. Considering the impact and relevance of ADHD in the child and adolescent populations at present, as well as the use of drugs for its control, it is imperative to have evidence of the highest quality for decision-making in clinical practice. To date, there is no evidence in Spanish that has synthesized and analyzed this phenomenon. Based on the foregoing, the objective of this review is to analyze the most recent evidence of the association between cardiovascular risk and pharmacotherapy in pediatric patients with ADHD. A literature search was conducted using the search terms "Cardiovascular Risk," "Attention Deficit Hyperactivity Disorder," and "Pediatrics," in addition to synonyms, which were combined with the operators "AND" and "OR," in the PubMed, ScienceDirect, Web of Science, and MEDLINE databases. After reviewing the most recent literature, it was identified that the quality of the current evidence regarding the association between increased cardiovascular risk secondary to pharmacotherapy in children and adolescents with ADHD is very low, heterogeneous, and fragmented. Nevertheless, the trend suggests that there may be a potential risk of the alteration of hemodynamic parameters, essentially heart rate and blood pressure, without involving the frequent or significant occurrence of serious cardiovascular adverse events. However, the evidence suggests continuous monitoring.